Determination of Palladium in Water by FAAS after Preconcentration and Separation with the Modified Barium-Strontium Titanate Powder by Dithizone - Zhang, Dong; Yu, Ping (Asian Journal of Chemistry, 2011)
A new method of preconcentration and separation with the modified barium-strontium titanate powder by dithizone (dithizone-BST) combined with flame atomic absorption spectrometry (FAAS) was proposed for the determination of trace palladium. The optimum experimental parameters for the adsorption and preconcentration of Pd(II), such as pH value of medium, contact time, eluent and coexisting ion, have been investigated. Moreover, the thermodynamics and kinetics of the adsorption were studied. The results showed that the Pd(II) could be quantitatively retained by the dithizone-BST in the pH range of 2 using hydrochloric acid, the adsorption time was 15 min and capability of adsorption was 21.135 mg g-1. The adsorption behaviour followed a Langmuir adsorption isotherm and a pseudo-second-order kinetic model, the adsorption was an endothermic and spontaneous physical process. The Pd(II) adsorbed on the dithizone-BST could be completely eluated by using ethylenediamine and sodium hydroxide mixture. The detection limit of this method for Pd(II) was 0.22 μg/L and the enrichment factor was 100. The method has been applied to the determination of trace amounts of Pd(II) in water with satisfactory results.